Dawn of the electronic age electrical technologies in the shaping of the modern world, 1914 to 1945 / Frederik Nebeker. - Nebeker, Frederik (Wiley ; Institute of Electrical and Electronics Engineers, 2009)
Much of the infrastructure of today's industrialized world arose in the period from the outbreak of World War I to the conclusion of World War II. It was during these years that the capabilities of traditional electrical engineering became ubiquitous. Even more importantly, it was during this time that a new type of electrical engineering--electronics--emerged. Because of its applications in communications, entertainment, industry, science and medicine, and the military, the electronics industry became a major part of the economy. Dawn of the Electronic Age explores how this engineering knowledge and its main applications developed in various scientific, economic, and social contexts, and explains how each was profoundly affected by electrical technologies. It takes an international perspective and a narrative approach, unfolding the story chronologically. --from publisher description.